Activity Report. Scoping activity for integration of Fish and Livestock systems. Prey Veng, Cambodia, 4–6 June 2025 - Philp, Joshua Neil Monty; Sean, Vichet; Sok, Sao; Tuy, Sinak; Otieno, Mary Atieno; Sok, Sophearith; de Silva, Sanjiv; Peters, Michael (2025)
During the inception meeting of the CGIAR Sustainable Animal and Aquatic Food (SAAF) Science Program, Cambodia and Laos were together identified as a potential hub for the integration of research activities related to aquaculture, forages and terrestrial livestock systems, under SAAF Area of Work 1 (AoW1). This potential for integration is derived from the concentration of existing capacity and research activities and the prevalence of smallholder mixed farms with diverse livelihood activities including cattle raising and aquaculture.